Questioning the Tax Treatment of Goodwill (GESTIÓN Y TENDENCIAS, 2017)
The current tax treatment of Goodwill and Badwill produces tax inequality. In the case of Goodwill, this is explained by the taxpayer's inability to recognize actual losses arising in a merger process until the organization recording them is dissolved or terminates its business activity. In the case of Badwill, it arises from the taxation of profits that may already have been taxed at source. These situations could give taxpayers an incentive to seek ways of avoiding potential internal double taxation, or to recognize, on justified grounds and in the short term, the losses generated in a given company merger process. One alternative for counteracting these effects is, through a legal amendment, to recognize the genuine right to use such losses and to seek a methodology allowing profits already taxed in their organizations of origin to be distinguished.